Women in the Aljafería - Cansado Berné, Mercedes; Gascón Ortiz, Teresa; Lozano Catalán, Rebeca (Filanderas, 2017)
During the Saturdays of January 2017 a series of guided tours was held in the Aljafería Palace under the theme «Women in the Aljafería», which arose as a result of the proposal of the team of guides of the palace to the Cortes de Aragón for Make different themed visits every month.